THE ROLE OF GREEN HOTEL POLICY IN IMPROVING EMPLOYEE GREEN BEHAVIOR: STUDY AT HOTEL ARUSS SEMARANG - Arinda Thira Novia Setiawan; Tri Retnaningsih Soeprobowati; Yanuar Luqman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The hospitality industry is recognized as one of the sectors that contributes significantly to environmental pressure due to instensive energy consumption, water use, and waste generation. In response to these challanges, many hotels have begun implementing environmental managemen policies known as Green Hotel Policies. These policies aim to support sustainable operational practices while encouraging environmentally responsible behavior among employees. This study aims toanalyze the implementation of Green Hotel Policy and examine Employee Green Behavior at Hotel Aruss Semarang, Indonesia. A mixed-methods approach combining descriptive quantitative and qualitative analysis was applied. Quantitative data were collected through questionnaires distributed to 58 hotel employees, while qualitative data were obtained through in depth interviews with hotel management, engineering staff, hotel guests, and community representatives. Descriptive statistical analysis was used to examine respondents’ perceptions regarding environmental policy implementation and employee green behavior. The results show that the implementation of Green Hotel Policy at Hotel Aruss Semarang is categorized as good across environmental, social, economic, and technological aspects. Employees demonstrate posistive green behavior particularly in energy conservation, waste management, and participation in environmental initiatives. Qualitative findings indicate that managerial commitment, environmental communication, and employee participation play important roles in strengthening environmentally responsible practices in hotel operations. Government regulations promoting sustainable tourism also reinforce the importance of environmental policy implementation within the hospitality sector. The study highlights that environmental policy integration within hotel managemen is essential for supporting sustainable tourism development and improving environmental responsibility in the hospitality industry. Keywords: Green Hotel Policy, Employee Green Behavior, Sustainable Tourism, Environmental Management, Hospitality Industry